Mole's babies - Bedford, David, 1969- (Tiger Tales, 2012)
After observing how other animals around the farm make their new offspring happy, an expectant father mole flaps llike a bird, splashes like a duck, and hops like a bunny until he discovers that his babies need just one thing--love.